(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objective: To correlate protease-producing Bacillus spp with physicochemical parameters from slaughterhouse soils. Methods: In this study, eight soil samples were collected from three slaughterhouses located in the Kathmandu Valley and designated as K1, 2, L1-3, and B1-3. Sterile methods were employed to collect the samples, and their physicochemical properties, including temperature, pH, moisture, electrical conductivity, alkalinity, and nutrients, were analyzed. This was followed by enrichment and isolation of protease-producing Bacillus spp. Results: The collected soils were pale to neutral grey and had alkaline pH. The soils contained moderate water, up to 14%. Even with low organic matter, it had high nitrogen levels. This study isolated Bacillus spp that produce proteases and measured the specific protease activity. Conclusion: Protease-producing Bacillus found in soils are directly proportional to the nutrients, especially in soils with higher nitrogen levels, which tend to have a greater abundance of protease bacteria. This indicates that soil fertility influences bacterial protease functions.